China and Africa
XIII, 403 p. 3 illus.
Keywords: This book investigates the expanding involvement of China in security cooperation in Africa. Drawing on leading and emerging scholars in the field, the book uses a combination of analytical insights and case studies to unpack the complexity of security challenges confronting China and the continent. It interrogates how security considerations impact upon the growing economic and social links China has developed with African states.